Evaluation of the Role of Secretory Sphingomyelinase and Bioactive Sphingolipids as Biomarkers in Hemophagocytic Lymphohistiocytosis - Jenkins, Russell W. (Am J Hematol, 2013)
Hemophagocytic lymphohistiocytosis (HLH) is a rare systemic inflammatory syndrome that results from unrestrained immune cell activation. Despite significant advances in the understanding of the pathophysiology of HLH, interventions remain limited for this often-fatal condition. Secretory sphingomyelinase (S-SMase) is a pro-inflammatory lipid hydrolase that is upregulated in several inflammatory conditions, including HLH. S-SMase promotes the formation of ceramide, a bioactive lipid implicated in several human disease states. However, the role of the S-SMase/ceramide pathway in HLH remains unexplored. To further evaluate the role of S-SMase upregulation in HLH, we tested the serum of patients with HLH (n=16; primary=3, secondary=13) and healthy control patients (n=25) for serum S-SMase activity with tandem sphingolipid metabolomic profiling. Patients with HLH exhibited elevated levels of serum S-SMase activity, with concomitant elevations in several ceramide species and sphingosine, while levels of sphingosine-1-phosphate were significantly decreased. Importantly, the ratio of C(16)-ceramide:sphingosine was uniquely elevated in HLH patients that died despite appropriate treatment, but remained low in HLH patients that survived, suggesting that this ratio may be of prognostic significance. Together, these results demonstrate upregulation of the S-SMase/ceramide pathway in HLH, and suggest that the balance of ceramide and sphingosine determine clinical outcomes in HLH.